Preparation and characterization of conductive poly-dl-lactic-acid/tetra-aniline conduit for peripheral nerve regeneration. (March 2019) - Guo, Xing-Lei; Xu, Hai-Xing; He, Qun-Di; Yu, Yun-Xuan; Ming, Xiao-Fei; Zheng, Fu-Rong; Wang, Xiao-Bin; Huang, Zhi-Jun; Zhao, Meng; Xu, Pei-Hu
Defected peripheral nerve regeneration is still a challenge in clinical treatment. Conductive polymers show great potential in nerve tissue engineering because of their electrical property based on bioelectricity in vivo. In this study, conductive composite nerve conduit was synthesized with tetra-aniline and poly-dl-lactic acid. Their properties and the differentiation of rat pheochromocytoma 12 (PC12) cells in vitro stimulated with 200 mV for 1 h were investigated. Different amounts of tetra-aniline (0%, 5%, 10%, and 15%) were used to synthesize the conduits with different conductivities (0, 0.00625, 0.01, and 0.025 s/m, respectively), tensile strengths (2.45, 3.40, 4.45, and 5.50 MPa, respectively), and contact angles (80°, 78.5°, 62.5°, and 61.5°, respectively). The percentage of neurite-bearing cells and the median neurite length increased with an obvious raise of the content of tetra-aniline. In addition, the conduit with subcutaneous implantable experiments in vivo showed less inflammatory response. These promising results illustrated that this poly-dl-lactic acid/tetra-aniline conductive composite conduit had potential for nerve tissue engineering.